Photodynamic Therapy for Basal Cell Carcinoma in Recessive Dystrophic Epidermolysis Bullosa. (17th April 2011) - Lee, Myn Wee; Varigos, George; Foley, Peter; Ross, Gayle
Abstract : A 22-year-old male with recessive dystrophic epidermolysis bullosa with a large superficial and nodular basal cell carcinoma on his right forehead was treated with photodynamic therapy. The treatment was well tolerated, and the site healed well. Patients with epidermolysis bullosa are at increased risk of developing skin cancers, particularly squamous cell carcinomas. However, basal cell carcinomas are rare in recessive dystrophic epidermolysis bullosa. As patients with epidermolysis bullosa have recurrent blistering and poor wound healing, surgery may not be the optimal choice in treating skin cancers. We present this case to highlight that photodynamic therapy may be a helpful and safe technique in the treatment of superficial skin cancers in patients with epidermolysis bullosa, as an alternative to more radical methods.